2023
DOI: 10.26599/jac.2023.9220758
|View full text |Cite
|
Sign up to set email alerts
|

SnFe 2O 4/ZnIn 2S 4/PVDF piezophotocatalyst with improved photocatalytic hydrogen production by synergetic effects of heterojunction and piezoelectricity

Abstract: The polarized electric field inside piezoelectric materials has been proved to be promising technique to boost the photogenerated charge separation. Herein, a novel flexible SnFe2O4/ZnIn2S4/PVDF (P-SZ) film

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Furthermore, the VB edge potential of MIL-125(Ti) was 3.95 eV and the CB edge potential of CuS was −0.41 eV calculated by the equation (eq ). The band rearrangement between MIL-125(Ti) and CuS boosted the directional migration of photogenerated electrons from CuS to MIL-125(Ti), realized the spatial separation of carriers, and effectively inhibited their recombination. α h v = A false( hv E g ) n E NHE = E Ag / AgCl + 0.059 × pH E Ag / AgCl 0 E g = E VH E CH …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the VB edge potential of MIL-125(Ti) was 3.95 eV and the CB edge potential of CuS was −0.41 eV calculated by the equation (eq ). The band rearrangement between MIL-125(Ti) and CuS boosted the directional migration of photogenerated electrons from CuS to MIL-125(Ti), realized the spatial separation of carriers, and effectively inhibited their recombination. α h v = A false( hv E g ) n E NHE = E Ag / AgCl + 0.059 × pH E Ag / AgCl 0 E g = E VH E CH …”
Section: Resultsmentioning
confidence: 99%
“…From this result, it can be found that when SIS and ZFO are in contact, the electrons flow from ZFO to SIS, which can further prove that there is a strong interaction between SIS and ZFO, which contributes to the separation and transfer of photoinduced electron–hole pairs. 26,27…”
Section: Resultsmentioning
confidence: 99%
“…Sulfide metal semiconductors have gained prominence due to their excellent reduction performance and visible light response, attributed to their high potential and relatively narrow bandgap in the conduction band. For examples, CdS, 15–18 ZnIn 2 S 4 , 19–23 and ZnS 24,25 have been extensively employed in water splitting to produce hydrogen energy. CdS, a representative catalyst for PHE, necessitates sacrificial agents due to its low valence band position, resulting in wastage.…”
Section: Introductionmentioning
confidence: 99%